Infothela: Information technology at your doorstep - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Infothela: Information technology at your doorstep, Times of India, 15 November 2002 Kanpur - Scientists at IIT have developed a battery-powered ´infothela´ equipped with an assortment of Internet and telecom facilities to impart